Sikap Konsumen Dalam Pembelian Buah Pisang Cavendish di Pasar Modern Kota Bandar Lampung - Niluh Puji Okta Wahyuni; Irmayani Noer; Teguh Budi Trisnanto (Journal of Food System & Agribusiness, 2022)
Banana is a fruit that is widely consumed by the community. Cavendish banana is one of the interesting bananas to be bought by consumers. Many consumers did not know aboutCavendish bananas, so it made demand of cavendish decrease. Therefore, this study is aimedto identify the character of consumers, the process of making choices, and consumer attitudesto Cavendish bananas in the modern market of Bandar Lampung City. This study used surveymethods and questionnaires as research instruments. A total of 100 consumers from variousmodern markets in Bandar Lampung were involved in this study. The study data were analyzedusing Microsoft excels formulas. The findings showed that the characteristics of consumerswho bought Cavendish bananas were 70% women and 30% were men and high schoolgraduates were the most buyers with 45%. Then in the process of choosing Cavendishbananas, more than 50% of consumers chose Cavendish bananas for delicious taste and healthbenefit. The study also found that 90% of consumers will buy Cavendish bananas againbecause they provided health benefits.